2011
DOI: 10.1016/j.biomaterials.2011.07.066
|View full text |Cite
|
Sign up to set email alerts
|

Use of autologous blood-derived endothelial progenitor cells at point-of-care to protect against implant thrombosis in a large animal model

Abstract: Titanium (Ti) is commonly utilized in many cardiovascular devices, e.g. as a component of Nitinol stents, intra- and extracorporeal mechanical circulatory assist devices, but is associated with the risk of thromboemboli formation. We propose to solve this problem by lining the Ti blood-contacting surfaces with autologous peripheral blood-derived late outgrowth endothelial progenitor cells (EPCs) after having previously demonstrated that these EPCs adhere to and grow on Ti under physiological shear stresses and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 24 publications
(26 reference statements)
1
32
0
Order By: Relevance
“…BOECs are the progeny of bone marrow-derived circulating endothelial progenitor cells and emerging evidence supports their use in cell-based therapies for promoting postnatal vasculogenesis and clinical use in cardiovascular applications [23,24]. Differentiation of these cells may promote the formation of a healthy endothelium on vascular graft surfaces [13,25,26]. This work also investigates whether immobilized heparin will have a negative effect on smooth muscle cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…BOECs are the progeny of bone marrow-derived circulating endothelial progenitor cells and emerging evidence supports their use in cell-based therapies for promoting postnatal vasculogenesis and clinical use in cardiovascular applications [23,24]. Differentiation of these cells may promote the formation of a healthy endothelium on vascular graft surfaces [13,25,26]. This work also investigates whether immobilized heparin will have a negative effect on smooth muscle cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…The cells were fluorescently labeled prior to implantation with PKH26 (Sigma-Aldrich) [17]. Four pigs received IVC implants (grade 2; Tico Titanium, MI, USA, pre-sectioned and reassembled as previously described) [17]. …”
Section: Methodsmentioning
confidence: 99%
“…Ti tubes were directly inserted into the IVCs without use of an artificial graft following our established methods [17,22]. All four Ti tubes were seeded with autologous pBD-ECs (2.4 × 10 6 cells/ml in 4.5 ml of medium) derived with the DWBI method; however, in two of the four implants the cells had additionally been mobilized with AMD3100 (0.5 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Our prior work has shown that these cells protect against thrombosis in vivo in a porcine model utilizing smooth Ti implantable devices. 19 …”
Section: Introductionmentioning
confidence: 99%